COLLABORATIVE SUPPLY CHAIN MANAGEMENT (SCM) TOOLS FOR IMPROVED TEAMWORK IN CONSTRUCTION PROJECTS - Mohd Nawi, Mohd Nasrun; Mehdi Riazi, Salman Riazi; Salleh, Nurul Azita; Ahmad, Mohd Akhir (International Journal of Supply Chain Management, 2019)
Fragmentation or the separated working environment has been a major hinderance to effective collaboration among construction industry players and these has been mainly blamed upon the wasteful conventional working practice. Supply Chain Management (SCM), which hold tightly on the notion of collaboration being among its most important enabler and has also proven to contribute to many important elements of an effective collaboration such as better trust, transparency, knowledge sharing, pain-gain sharing etc.; has therefore been promoted to overcome the problem via numerous Collaborative Tools it has to offer. This paper presents part of an on-going research aimed at using SCM Tools to overcome delay and definitely collaboration is an aspect that needs improvement. After conducting a comprehensive literature reviews on past proposal and applications, a number of SCM Collaborative Tools have been identified, elaborated and discussed in this paper; which is expected to serve as a guide towards adopting SCM into construction project practices and thus, achieve the benefits it has to offer. Some of them have been applied in major projects and experienced success hence, deserve more appreciation by the construction world.